Do Unsafe Tetanus Toxoid Injections Play a Significant Role in the Transmission of HIV/AIDS? Evidence from Seven African Countries - de Walque, D. (2012)
OBJECTIVES: Although sexual transmission is generally considered to be the main factor driving the HIV/AIDS epidemic in Africa, recent studies have claimed that iatrogenic transmission should be considered as an important source of HIV infection. In particular, receipt of tetanus toxoid injections during pregnancy has been reported to be associated with HIV infection in Kenya. The objective of this paper is to assess the robustness of this association among women in nationally representative HIV surveys in seven African countries. METHODS: The association between prophylactic tetanus toxoid injections during pregnancy and HIV infection was analysed, using individual-level data from women who gave birth in the past five years. These data are from the nationally representative Demographic and Health Surveys, which included HIV testing in seven African countries: Burkina Faso 2003 (N = 2424), Cameroon 2004 (N = 2600), Ethiopia 2005 (N = 2886), Ghana 2003 (N = 2560), Kenya 2003 (N = 1617), Lesotho 2004 (N = 1278) and Senegal 2005 (N = 2126). RESULTS: Once the odds ratios (OR) were adjusted for five-year age groups and for ethnic, urban and regional indicators, the association between prophylactic tetanus toxoid injections during pregnancy and HIV infection was never statistically significant in any of the seven countries. Only in Cameroon was there an association between previous tetanus toxoid injection and HIV positivity but it became weaker (OR 1.53, 95% CI 0.91 to 2.57) once urban location and ethnic group were adjusted for. CONCLUSIONS: Although the risk of HIV infection through unsafe injections and healthcare should not be ignored and should be reduced, it does not seem that there is, at present and in the seven countries studied, strong evidence supporting the claim that unsafe tetanus toxoid injections are a major factor driving the HIV epidemic.